Breaking blades: Experimental programme on intentional fracturing systems of lithic tools. (2016) - , M. Cristina López-Rodríguez; , Ignacio Martín-Lerma; , Juan A. Marín de Espinosa Sánchez; Sáez, Carmen Gutiérrez
No abstract available